Simulasi Sistem Antrian Pembelian Tiket Kereta Api Menggunakan Aplikasi Promodel (Studi Kasus di Stasiun Purwakarta) - Diki Muchtar; Puspita Hadi Putri; Iman Thoriq; Wanwan Jamaludin (Journal of Management and Industrial Engineering (JMIE), 2024)
Purwakarta Station, as one of the busiest train stations in Indonesia, often experiences passenger congestion, especially during peak hours. Not only does this cause inconvenience to passengers, but it can also pose a safety risk. The purpose of this study is to improve the efficiency and safety of train passenger queues. This research uses Promodel software. The results of this study found that there was no waiting presentation and down presentation. Meanwhile, there is a percentage of delay in the location of entering the counter and exiting the counter. Presentations were blocked by 4.47% and the percentage of counter exit was 52.89%. This means that there is no significant buildup in the simulation of the train ticket purchase queue system at Purwakarta Station).